Men’s Sheds: Australia’s gift to the world - Golding, Barry (Adult Education Discourses, 2023)
This paper provides a window into recent developments in the international Men’s Shed movement up to 2022. It includes useful insights into the complex, fascinating and still evolving role that gender plays in Sheds, and is essential for understanding where the 25 year old Men’s Shed movement and also the decade old Women’s Shed movement, both originating in Australia, might be headed, and perhaps how it might take root in Poland or elsewhere in mainland Europe. The paper also explores what it is about Men’s Sheds which is so attractive to older men and particularly how it informally enhances their learning and wellbeing. I have also included a brief reflection on some of the professional and personal factors which attracted me to research Sheds internationally, and to since become a Shed advocate and an Australian Men’s Shed Patron.